Improving Public's Knowledge of Cardiovascular Health through Health Education - Risnandar, Mochammad Wisnu; Anna, Anastasia; Mirwanti, Ristina (Media Karya Kesehatan, 2024)
Cardiovascular disease in Indonesia has undergone a vast epidemiological transition in the last three decades, with an increase in the number of deaths and disabilities, resulting in the disease burden and high healthcare costs. Community empowerment strategies through educational and participatory approaches are part of efforts to prevent and control cardiovascular disease. A health education program called "Quality Life with a Healthy Heart" was held with the aim of improving public’s knowledge, especially in West Java, in recognizing cardiovascular diseases (primarily coronary heart disease) and efforts to prevent them and in providing initial assistance for out-of-hospital cardiovascular emergencies. Up to 148 people participated in the program via online videoconferencing and streaming media platform. Participants' level of knowledge was evaluated before and after participating in the program with an electronic questionnaire consisted of 8 multiple choice inquiries. Data were analyzed from 27 participants who completely filled out the pre-test and post-test questionnaires after received four session health education on webinar using descriptive statistics and the non-parametric Wilcoxon Signed Ranks test. Results showed that as many as 59.3% of participants had good knowledge at the pre-test, while 85.2% of participants had good knowledge at the post-test. There was a significant difference between participants' level of knowledge before and after receiving the health education (Z = -3.933, p<0.001). It can be concluded that the program improved public's knowledge of cardiovascular health. Further educational initiatives are recommended to facilitate community skills in providing first aid for cardiovascular emergencies through Basic Life Support. Optimizing the use of social media can be an option to increase public health literacy. Keywords: Cardiovascular disease, health education, knowledge, public.